A versatile and accessible polymer coating for functionalizable zwitterionic quantum dots with high DNA grafting efficiency. Issue 74 (27th August 2019) - Grazon, Chloé; Chern, Margaret; Ward, Katherine; Lecommandoux, Sébastien; Grinstaff, Mark W.; Dennis, Allison M.
Abstract : An accessible method to produce a click chemistry-ready, zwitterionic polymer from commercially available reagents facilitates efficient DNA grafting to quantum dots. Abstract : Efficient and versatile functionalization of poly(anhydride maleic- alt -isobutylene) (PIMA), with economical commercial reagents, results in the one-step/one-day production of a copper-free click chemistry-ready carboxybetaine-like coating for quantum dots (QDs). The QDs are bright and stable in aqueous media and easily grafted with DNA with >95% efficiency.